2015
DOI: 10.1109/tla.2015.7404939
|View full text |Cite
|
Sign up to set email alerts
|

Using Design Patterns as Usability Heuristics for Mobile Groupware Systems

Abstract: The objective of this research was to determine the capability of design patterns to find usability issues in mobile groupware interfaces. A particular collection of patterns was used for this purpose. Patterns were obtained by identifying essential activities and collaborative tasks in the communication process among members of working groups. A previous study on said proposal suggested that design solutions offered by the patterns foster communication, collaboration, and coordination through user interface e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Considering the previous definitions, the second point of the initial PROMETHEUS validation consists in analyzing the data from the 19 studies identified by [8] that attempt to determine the effectiveness of the new heuristics (Section II), and considering two additional recently-published studies [5], [18]. We calculate the heuristic quality indicators for each of them as possible according to the published information, and we underscore the conclusions regarding whether or not the developed heuristics are more effective than the control heuristics.…”
Section: B Validation Of Quality Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the previous definitions, the second point of the initial PROMETHEUS validation consists in analyzing the data from the 19 studies identified by [8] that attempt to determine the effectiveness of the new heuristics (Section II), and considering two additional recently-published studies [5], [18]. We calculate the heuristic quality indicators for each of them as possible according to the published information, and we underscore the conclusions regarding whether or not the developed heuristics are more effective than the control heuristics.…”
Section: B Validation Of Quality Indicatorsmentioning
confidence: 99%
“…One of the most widely used inspection methods is heuristic evaluations, proposed by Nielsen and Molich [4]. In this method, a small group of 3-5 evaluators inspect a particular software system's usability, guided by a list of usability criteria known as usability heuristics [4], [5]. Heuristic evaluation is a low-cost easily applicable method, which can be used at various stages of an application's development [4].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, we have witnessed significant advances in wireless technology and the ubiquity of mobile devices with increasing processing, storage, and communication capabilities. This evolution of mobile computing has opened up new possibilities in the fields of communication, social interaction, and learning [1]. The increase in the number of mobile users and the variety of tasks possible through these devices has made it crucial to offer a harmonious experience of interacting with mobile interfaces.…”
Section: Introductionmentioning
confidence: 99%